Oropharyngeal Colonization by Streptococcus pneumoniae among Medical Students in Indonesia - Valencia, Stella; Mulyana, Yanti; Dhianawaty, Diah (Althea Medical Journal, 2016)
Background: Streptococcus pneumoniae may colonize the upper respiratory tract without causing any symptoms. Medical students may be inhabited by these bacteria and transmit them to patients who were prone to infections. Streptococcus pneumoniae resistance to antibiotics was recently reported. This study was conducted to determine whether there was Streptococcus pneumoniae colonization among Medical Students of the Faculty of Medicine Universitas Padjadjaran Batch 2011 and analyze its susceptibility patterns towards several antibiotics.Methods: A descriptive study was conducted involving 75 Medical Students of the Faculty of Medicine Universitas Padjadjaran Batch 2011 that met the selection criteria. After informed consent, oropharyngeal throat swab was taken and further identification was carried out. Once Streptococcus pneumoniae colony was identified, susceptibility testing would be performed.Results: The identification results indicate that 7 students (9%) were colonized by Streptococcus pneumoniae. The susceptibility test showed that out of 7 isolates, 2 were resistant to 1 antibiotic, 1 was resistant to 2 antibiotics, and 4 were resistant to 3 antibiotics. Meanwhile, Streptococcus pneumoniae was resistant to trimethoprim-sulfamethoxazole (71%), oxacillin (71%), erythromycin (57%), and levofloxacin (14%).Conclusions: Streptococcus pneumoniae colonization is found among medical students. All Streptococcus pneumoniae are resistant to one or more antibiotics, mostly to trimethoprim-sulfamethoxazole and oxacillin. [AMJ.2016;3(3):349â54]Â DOI: 10.15850/amj.v3n3.878Â